Analisa Nilai OTTV (Overall Thermal Transfer Value) pada Bangunan Pemerintahan di Kota Lhokseumawe - Hasanah, Dita; Safyan Yahya, Adi; Saputra, Eri (Jurnal Etnik: Ekonomi-Teknik, 2023)
Global warming and the energy crisis are the biggest problems in the world today, many efforts must be made to avoid them. One of them is by continuing to increase the implementation of energy efficient buildings. In Indonesia, energy-efficient buildings must meet the requirements set out in SNI 03-6389-2020 where the maximum limit for the OTTV (Overall Thermal Transfer Value) value is 35 Watt/m² and has been enforced by the Government from now on. However, these requirements have not been fully fulfilled by investors, as well as planning agencies or consulting units. There are still many buildings whose OTTV value is not yet known. As is the case with the object of this research, namely the Lhokseumawe Mayor's Office building. This research aims to calculate and determine the OTTV value for the research object of the Lhokseumawe Mayor's Office building, so that later it will be known whether the building is categorized as an energy efficient building or not. The research method used is an experimental quantitative method using the OTTV Microsoft Excel spreadsheet calculator from the Ministry of Public Works and Public Housing (BGH-PUPR). The results of this research analysis show that the Lhokseumawe Mayor's Office building has many large openings and has sunlight fenestration, so that the overall OTTV value on the building envelope is below the SNI standard threshold of 35 Watt/m² and can be categorized as an energy efficient building.